A photo-degradable injectable self-healing hydrogel based on star poly(ethylene glycol)-b-polypeptide as a potential pharmaceuticals delivery carrier. Issue 36 (6th September 2018) - Zhao, Dinglei; Tang, Quan; Zhou, Qiang; Peng, Kang; Yang, Haiyang; Zhang, Xingyuan
Abstract : As one of the most promising biomaterials, injectable self-healing hydrogels have found broad applications in a number of fields such as local drug delivery. Abstract : As one of the most promising biomaterials, injectable self-healing hydrogels have found broad applications in a number of fields such as local drug delivery. However, controlled release of drugs in hydrogels is still difficult to realize up to now. Here, we report a novel photo-degradable injectable self-healing hydrogel based on the hydrophobic interaction of a biocompatible four-arms star polymer, poly(ethylene glycol)- b -poly(γ- o -nitrobenzyl-l -glutamate). The hydrophobic interaction between poly(γ- o -nitrobenzyl-l -glutamate) not only connects poly(ethylene glycol)- b -poly(γ- o -nitrobenzyl-l -glutamate) together with a crosslink but also provides a hydrophobic domain to encapsulate hydrophobic pharmaceuticals such as doxorubicin (DOX). Due to the dynamic character of the hydrophobic interaction, the hydrogel exhibits excellent injectable and self-healing ability. In particular, the photolabile o -nitribenzyl ester group is cleaved under UV irradiation. As a result, the hydrophobic domain transforms into the hydrophilic one and the embedded DOX is released effectively. An increasing release ratio of DOX dramatically enhances the apoptosis ratio of HeLa cells. We expect these attractive properties may be beneficial to practical applications of the hydrogel as an effective local drug delivery means in a truly physiological environment.